Drying Process Modeling and Quality Assessments Regarding an Innovative Seed Dryer - Arsenoaia, Vlad Nicolae; Roșca, Gheorghe Radu; Cârlescu, Petru; Băetu, Marius; Rațu, Roxana; Veleșcu, Ionuț; Țenu, Ioan (Agriculture (Basel), 2023)
The dehydration of agricultural products is a topic of research covering the preservation and conservation of the quality of agricultural and food items. The actual tasks of environmental protection include creating novel solutions to reduce the energy needs and exothermic consequences of the bulk of industrial processes. Due to the fact that air temperature and velocity in the seed layer are not uniform, the currently employed seed dryers have significant energy requirements and generate a lot of heat. A device that addresses this problem was developed and is now the subject of a patent application. The Coandă effect-based tronconic plates used in the dryer enable warm air to be dispersed uniformly throughout the product mass. Mathematical modeling was used for the design, operation, and optimization of the baffled drying unit. The investigations, which were conducted by modifying and observing the operational parameters (the velocity and temperature of the warm air) used four distinct types of seed with three different beginning moisture concentrations. Following the completion of the CFD simulation, the unit’s design was created in SolidWorks. The seed and air humidity were measured using sensors, and the air speed was measured using an anemometer. The current lines and fields were used to express the speed and temperature results. The unit with deflectors reduced the amount of heat released by up to 15.38% and reduced the amount of energy used by up to 14%.